Long-term underfed dry, non-pregnant Balady goats can better reduce their energy expenditure than Shami goats - Askar A.R. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Twenty-four adult non-productive females, 12 Balady and 12 Shami goats, were employed to evaluate effects of nutrient restriction on energy expenditure (EE) and energy balance (EB). Animals were individually housed for a 3-month period and then moved to metabolic cages in two sets of 12 animals, three per treatment and breed for each set. Six animals of each breed were fed a concentrate mixture and alfalfa hay diet (1:1 as DM basis) at a level adequate for the metabolizable energy (ME) of maintenance (MEm, C). The other six were fed 50% of this amount relative to actual body weight (R). Energy expenditure was estimated by heart rate (HR) monitor after individual calibration by oxygen consumption with a face mask open-circuit respiratory system. Digestible energy was negatively affected (-10 pts) by restricted feeding, without significant differences between goat breeds. Energy expenditure was greater (P<0.001) for C vs R and higher (P<0.01) for Shami vs Balady goats. As a result, the EB was similar between both goat breeds fed near maintenance , while it was lesser unbalanced (P<0.05) in Balady vs Shami goats when underfed. In conclusion, Balady goats, but not Shami goats, had the ability to reduce their EE in order to improve their EB as a mechanism of adaptation when their ME intake is restricted below MEm requirements for a long time.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)